Spatiotemporal epidemiology of Japanese encephalitis cases of Dibrugarh district from 2014 to 2018: A hospital record-based descriptive study - Monuj Kurmi; Jenita Baruah (Wolters Kluwer Medknow Publications, 2022)
Background: Since 1976, several JE outbreaks have been reported from most of the districts of Assam. Objectives: The present study aims to conduct a descriptive and spatial analysis to understand the spatiotemporal distribution of JE cases of Dibrugarh district. Methods: Spatiotemporal distribution of JE cases from 2014 to 2018 at village level was described in maps using Geographical Information System. Spatial association between JE reporting places in the study area has been analyzed using spatial statistics analytical techniques. Temporal distribution of JE cases from 2014 to 2018 for different variable were described in tables. Results: During the period 2014-2018, incidence rate of JE cases ranged between 2.7/100,000 and 5.9/100,000 population and highest case fatality rate was 18.3% in 2014. Highest numbers of JE cases were reported in the age group 0-10 years. Most of the JE cases were from rural areas (84.2%). There was a seasonal pattern of JE which peaked in July. There were hotspots around Dibrugarh Municipality area, Duliajan oil town, Hatiali gaon, Naharkatiya chah bagicha, Nagaon Dhadumia gaon, and Nahortoli Tea Estate. Conclusion: On the basis of the study, JE hotspots can be identified that would help health authorities to further investigate and identify the factors responsible for its occurrence.